Rule of Law and role of the Constitutional Court of the Republic of Croatia in enforcing administrative and administrative court rulings - Mario Jelušić; Duška Šarin (Zbornik Radova Pravnog Fakulteta u Splitu, 2015)
The Constitutional Court of the Republic of Croatia does not have direct authority in the enforcement of various administrative and administrative court rulings. However, the institute of constitutional legal action by which the fundamental rights and freedoms are guaranteed by the Constitution of the Republic of Croatia places the Constitutional Court in the position of deciding on the protection of these rights which could be infringed during proceedings and in the enforcement of court decisions reached in administrative proceedings and administrative disputes and must simultaneously be included also in the enforcement of decisions by administrative bodies and the judicial judgements by administrative courts. Within the protection of fundamental constitutional rights and freedoms concerning the enforcement of administrative and administrative judicial decisions, the role of the Constitutional Court in protecting the wider legal political concept of the rule of law as one of the fundamental and initiatory values of the constitutional order of the Republic of Croatia, is exceptionally important. The legal political concept of the rule of law is marked by the system of political power which is founded on respecting the Constitution, the law and other regulations simultaneously and on the part of citizens and on the part of the bodies of governmental power. In this sense, all general legal acts (provisions), as well as certain acts of government bodies, must be founded on the Constitution, law and other provisions and considered more widely, the right to enforcement of administrative judicial decisions emerges from the right to access the court. The enforcement of administrative and administrative judicial decisions is the last phase of the administrative procedure, that is, administrative dispute. It establishes the state which determines in the disposition of the act it enforces. Enforcement in administrative proceedings is carried out against the person who is bound to fulfil the obligation ( enforcee), that is, its legal successor. It is implemented officially (ex officio) when public interest orders it. Enforcement which is in the party’s interest is implemented at the suggestion of the party (enforcement applicant) and can be implemented on the basis of the parties’ negotiation. Enforcement of the judgement where the administrative court resolves the issue must be ensured by the defendant.